Optimalisasi Kompetensi Pedagogik Guru Pendidikan Agama Kristen dalam Penerapan Metode Pembelajaran Berbasis Masalah Pada SMP Negeri 4 Pagaran - Eva Siambaton (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This study aims to explore the optimization of pedagogical competence of Christian Religious Education (PAK) teachers in the application of problem-based learning (PBM) methods at SMP Negeri 4 Pagaran, North Tapanuli Regency. Teachers' pedagogical competence has a crucial role in designing and implementing effective learning processes, especially in the context of implementing PBM methods that aim to improve students' critical thinking and problem-solving skills. This study uses a qualitative research method with a library approach from book and journal theories to explore information on how PAK teachers implement their pedagogical competence in PBM. The results of the study indicate that PAK teachers at SMP Negeri 4 Pagaran have optimized their pedagogical competence in adapting the PBM method by focusing on the characteristics of student development which is carried out with a more personal approach. This study concludes that increasing training and development of pedagogical competence for PAK teachers through the application of PBM methods is very effective in improving the quality of learning at SMP Negeri 4 Pagaran.